Perceptions of Students Regarding the Impact of Occupational Stress on Teachers’ Performance at Public Sector Universities of Balochistan (Journal of Social Sciences Review, 2023)
This study aimed to investigate students' perceptions regarding the influence of occupational stress on teachers' performance at public sector universities in Balochistan. The objectives included examining how students perceive occupational stress affecting teachers' subject knowledge, teaching skills, classroom management, and evaluation abilities. The study involved 267 students majoring in social sciences from four public sector universities (UOB, BUITEMS, UOL, and SBK) in the Quetta and Loralai divisions. A probability sampling technique randomly selected 223 students from the accessible population. Data collection utilized a closed-ended questionnaire with 20 Likert scale items. The data were analyzed using percentages and chi-square tests. The findings indicated that a significant number of participants believed that occupational stress negatively impacts teachers' subject mastery, lecture preparation, fair treatment of students, creativity, compassion toward students, motivation for teaching and learning, and the use of various teaching methods. Based on these results, recommendations include providing physical facilities to reduce teachers' occupational stress, organizing capacity-building workshops for both new and experienced teachers to manage stress, and adjusting teachers' salaries to accommodate inflation.
Keywords: Occupational Stress; Anxiety; Depression Mastery of Subject Matter Knowledge; Teaching Skills; Classroom Management Skills; Evaluation Skills